2000
DOI: 10.1002/1097-0290(20001005)70:1<54::aid-bit7>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of two-step models in estimating nitrification kinetics from batch respirograms under different relative dynamics of ammonia and nitrite oxidation

Abstract: A mechanistically based nitrification model was formulated to facilitate determination of both NH 4 + -N to NO 2 − -N and NO 2 − -N to NO 3 − -N oxidation kinetics from a single NH 4 + -N to NO 3 −-N batch-oxidation profile by explicitly considering the kinetics of each oxidation step. The developed model incorporated a novel convention for expressing the concentrations of nitrogen species in terms of their nitrogenous oxygen demand (NOD). Stoichiometric coefficients relating nitrogen removal, oxygen uptake, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…This is particularly the case considering the heterogeneity of the nitrifying microbial consortium under study. An alternative to the unavailability of X A and X N measurements is to estimate them as fractions of the total biomass concentration according to stoichiometric considerations [1,5] or to consider the nitrification kinetics in terms of volumetric rather than specific oxidation rates. In this work, the volumetric rate of ammonium oxidation r NH 4 = q NH 4 X A , of nitrite oxidation r NO 2 = q NO 2 X N and benzene transformation r BZ,A = q BZ,A X A was introduced.…”
Section: A Two-step Nitrification With Benzene Transformationmentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly the case considering the heterogeneity of the nitrifying microbial consortium under study. An alternative to the unavailability of X A and X N measurements is to estimate them as fractions of the total biomass concentration according to stoichiometric considerations [1,5] or to consider the nitrification kinetics in terms of volumetric rather than specific oxidation rates. In this work, the volumetric rate of ammonium oxidation r NH 4 = q NH 4 X A , of nitrite oxidation r NO 2 = q NO 2 X N and benzene transformation r BZ,A = q BZ,A X A was introduced.…”
Section: A Two-step Nitrification With Benzene Transformationmentioning
confidence: 99%
“…Eqs. (5) and (6) correspond to Monod equations when S BZ = 0. Some authors have suggested that this kind of negative effect is probably due to the harmful effect of hydrocarbons on the functioning of biological membranes [18][19][20][21][22][23].…”
Section: Toxic Effect Of Benzenementioning
confidence: 99%
See 1 more Smart Citation
“…The assay also uses custom built graphical user interface software to facilitate respirometric data acquisition and kinetic parameter estimation. A complete description of the laboratory assay is presented by Chandran and Smets (2000). The work described here used a modified assay design to measure nitrification inhibition in actual activated sludge.…”
Section: Novel Respirometric Assay For Measuring Nitrification and Nimentioning
confidence: 99%
“…The discussion of nitrite (S NO 2 Þ variation was absent in theses models. Of course, some two-stage nitrification models [7][8][9][10][11][12][13][14][15] and some multi-stage denitrification models [8,16] were proposed too. Although these models could predict nitrification or denitrification successfully, the application of these models were merely related to nitrogen removal.…”
Section: Introductionmentioning
confidence: 99%